Health-related quality of life before and after hematopoietic stem cell transplant: evidence from a survey in Suzhou, China. Issue 9 (21st October 2018) - Liang, Yongchun; Wang, Haifang; Niu, Meie; Zhu, Xiaming; Cai, Jianzheng; Wang, Xiubei
ABSTRACT: Objectives: The aim of our longitudinal study was to explore changes in HRQOL over a 6-month period and to identify factors associated with the HRQOL of HSCT recipients. Method: Our study comprised 191 HSCT patients; their data were collected before transplantation and at 30, 90, and 180 days posttransplantation. The Functional Assessment of Cancer Therapy-Bone Marrow Transplant (FACT-BMT) questionnaire was used to assess HRQOL.We also evaluated the patients' demographic characteristics and clinical histories to determine the relative contributions of these factors to HRQOL outcomes. Results: Before HSCT, the patients reported a mean overall HRQOL of 110.31 (SD, 14.99); this reached a minimum of 105.07 (SD, 18.85) at day 30 after HSCT and increased steadily over time to 106.71 (SD, 18.34) at day 90 and 108.16 (SD, 18.34) at day 180 after HSCT.Compared with baseline, overall HRQOL changed with the mean of −5.24 (SE 1.55; P  = .001), and −3.60 (SE 1.55; P  = .022), respectively, at 30 days and 90 days after HSCT. Overall HRQOL returned to near pretransplant levels at 180 days after HSCT (SE 1.47; P  = .146).Generalized estimating equation (GEE) models showed that household income ( β  = 6.590; P  < .001), transplant-related complications ( β  = −6.101; P  < .001), and patient age ( β  = 0.243, P  = .045) were associated with HRQOL. Conclusion: The patients' overall HRQOL was severely impaired in the early stages of posttransplantation, and patients experienced the worst HRQOL at 30 days. They had improved significantly by 180 days posttransplantation. We also found that household income, transplant-related complications, and age were independent predictors of early HRQOL.We therefore concluded that the HRQOL of HSCT patients in the early stages posttransplantation deserved more attention.